REGULATORY MECHANISMS OF UKRAINIAN PHARMACEUTICAL MARKET COMPETITIVENESS IN THE CONTEXT OF EUROPEAN INTEGRATION - Honchar, Vadym; Budnikevich, Iryna (Three Seas Economic Journal, 2020)
The purpose of the paper is to summarize and present the differences in the competitive environment of the European Union (EU) and Ukrainian pharmaceutical markets. The method of longitudinal study allowed to detect the patterns of changes and correlations for pharmaceutical products exports and imports volumes over twenty years (2001-2020). Methodology. The research is based on the definition of the pharmaceutical market as a complex socio-economic institution that fulfills the function of pricing medical products and utilizes them to ensure health care functioning. It indicates the population’s wellbeing and requires ongoing maintenance based on needs agreement of households, economic entities, and the state. The quantitative research is based on export-to-import coverage ratio calculations with the identification of pharmaceutical products fraction in the total volume of foreign trade, including the one with the EU. The results of the paper consist in the evaluation of the competitive environment of the European Union’s pharmaceutical market and statistical assessment of Ukrainian foreign trade of pharmaceutical products. They also include the definition of the European integration influence over the Ukrainian pharmaceutical market and well-reasoned recommendations about the application of the state and trade regulation mechanisms. In the paper, we defined the distinctive features of the European countries’ pharmaceutical markets and outlined their main characteristics that have connections to the transnational corporation’s activities, common market, and high concentration. Statistical data collected over 20 years indicated the dynamic development of the Ukrainian pharmaceutical market, despite its small-scale contribution to the foreign trade turnover. The dependence of Ukraine on the foreign supplies of drugs and medications is illustrated by the multiple excesses of imports over exports, especially in the trade relationships with the EU. The EU countries are the leading importers of pharmaceutical products to the Ukrainian market. However, the share of medical supplies exports from Ukraine to the EU countries is negligible. Their key exporters are post-Soviet and developing countries. The growth in Ukraine’s export potential is inextricably linked to the expansion of the competitiveness of domestic medical supplies. Practical implications consist in the development of recommendations concerning the GMP and GDP demands realization, domestic manufacturers cooperation with the leading foreign pharmaceutical companies, the penetration of transnational companies into the Ukrainian domestic pharmaceutical market based on imports of innovative technologies, the improvement of the marketing management of the pharmaceutical products exporting. The priority factor in the growth of the competitiveness of the Ukrainian pharmaceutical market is a successful combination of state and trade regulation mechanisms. The objects of these factors are the pricing policy for material resources and finished products, the introduction of innovations, tax exemptions, and export-import quotas implementation. They also include the establishment of traffic rates that depend on the market saturation with socially significant medical supplies, budget support of the prioritized subsectors of the pharmaceutical industry, and patent protection. The expected results concern the decrease in the dependence of the Ukrainian pharmaceutical market on the foreign distribution of the raw materials and finished products and strengthening the positions of the Ukrainian manufacturers in foreign markets. Value/originality. We evaluated the competitiveness of the national pharmaceutical market based on the criteria of foreign trade performance and detected the priorities of its growth, taking into consideration the synthesis of the state and trade regulation mechanisms.
Keywords: competitiveness, pharmaceutical market, national economy, European integration, market, state regulation.